Pharmacotherapy for primary biliary cholangitis: an assessment of medication candidacy and rates of treatment - MacDonald, Nicholas; Loh, Rebecca; Fenkel, Jonathan M.; Sass, David A.; Halegoua-DeMarzio, Dina (BMC Gastroenterology, 2024)
Ursodeoxycholic acid is the preferred first-line therapy for primary biliary cholangitis. Alternative therapies, such as obeticholic acid, are recommended for patients who cannot tolerate ursodeoxycholic acid or who have an inadequate response to ursodeoxycholic acid monotherapy. Prior investigations have suggested that as many as 30% of patients with primary biliary cholangitis may have never received treatment with ursodeoxycholic acid. No prior investigations have examined usage rates of obeticholic acid in the treatment of primary biliary cholangitis.